Trace Elements in Abiotic and Biotic Environments - Kabata-Pendias, Alina (Taylor & Francis, 2015)
This book helps readers understand the fundamental principles and phenomena that control the transfer of trace elements. It describes the occurrence and behavior of trace elements in rocks, soil, water, air, and plants, and also discusses the anthropogenic impact to the environment. In addition, the book covers the presence of trace elements in feeds, as either contaminants or as nutritional or zootechnical additives, and their transfer across the food chain to humans. All trace elements are covered-from aluminum to zirconium-as well as rare-earth elements (actinides and lanthanides).